Conceptual foundations of inclusive educational paradigm - Давиденко, Ганна (Pedagogy of Higher and Secondary Education, 2014)
Davydenko H. V. Conceptual foundations of inclusive educational paradigm. The article deals with a research of conceptual bases of inclusion. Such philosophical principles of inclusive education as a new humanitarian social model of disability, a principle of including, a principle of an open indefinite personality, a concept “normalization”, a principle of evolution and total reforms at all levels of society have been defined and scientifically grounded.